Back pain in children and adolescents. Issue 12 (December 2015) - Ryder, Clive; Harrison, Kathryn; Johnson, Karl
Abstract: Back pain in childhood and adolescence is a common presentation. While the majority of cases have a benign aetiology, it can represent serious disease requiring prompt diagnosis and treatment. We aim to give an overview of the assessment of a child or adolescent presenting with back pain and the clinical features of the common and serious diagnoses. This article will provide practical advice on the approach to clinical assessment, investigation and management of back pain in children and young people.